Plagiarism: An essay in terminology - Satija, Mohinder Partap; Martínez-ávila, Daniel [UNESP] (Defence Scientific Information and Documentation Centre, 2019)
The terminology on plagiarism is not hard and fast. It is fluid, a bit ambiguous, and still emerging. It may take some time to settle the terms more clearly, concretely and exhaustively. This paper aims to provide a terminological discussion of some important and current concepts related to plagiarism. It discusses key terms/concepts such as copyright, citation cartels, citing vs. quoting, compulsive thief, cryptomnesia, data fakery, ignorance of laws and codes of ethics, information literacy, lack of training, misattribution, fair use clause, paraphrasing, plagiarism, plagiarism detection software, publish or perish syndrome, PubPeer, retraction, retraction vs. correction, retraction watch, salami publication, similarity score, Society for Scientific Values, and source attribution. The explanation and definition of these terms/concepts can be useful for LIS scholars and professionals in their efforts to fight plagiarism. We expect this terminology can be referred in future discussions on the topic and also used to improve the communications between the actors involved.
Keywords: Copyright; Cryptomnesia; Information literacy; Plagiarism; Research frauds; Retractions; Terminology management